(untitled) (Gestão & Regionalidade, 2022)
This paper aims at reaching an understanding on the standards applied in health regions of Brazil concerning both performance in health and socioeconomic conditions. In order to reach such, two cluster analyses of the current 438 health regions were used, composed of structural constraint indicators and health associated dimensions. The first cluster analysis employed the 3 indicators that constitute the structural constraints, while the second cluster analyses the 6 dimensions of health. The results demonstrate that the health regions with the worst values for structural constraints and financial performance, human resources, infrastructure and quality are located mainly in the macro regions of the North and Northeast of Brazil. In addition, 25% of the health regions in Brazil show a better performance in coverage and quality, and these can be found in the Southeast as well as Northeast regions. Therefore, the conclusion is reached that the regions of health in Brazil still undergo wide-reaching inequalities in regional health both in socioeconomic conditions and health performance.